2023
DOI: 10.3390/v15112217
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus Reactivation and Increased Vascular Risk in People Living with HIV: Data from a Retrospective Cohort Study

Deborah Fiordelisi,
Mariacristina Poliseno,
Nicolo’ De Gennaro
et al.

Abstract: Background: The increased vascular risk associated with varicella–zoster virus (VZV) reactivation is extensively established in the general population. This retrospective cohort study investigates whether this observation holds for People Living with HIV (PLWH), a group already confronting heightened cardiovascular risk. Methods: Among PLWH who initiated antiretroviral therapy (ART) at our center and have been under our care for >24 months since 1st January 2005, individuals with a history of herpes zoster … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…However, it was recently found that VZV reactivation is associated with an increased vascular risk in PLWH. 72 …”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently found that VZV reactivation is associated with an increased vascular risk in PLWH. 72 …”
Section: Discussionmentioning
confidence: 99%